Pelatihan Pembuatan Ecoprint Menggunakan Tekhnik Pounding Di Tolotongga, Kota Bima Nusa Tenggara Barat - Ditiyyah Hafidzah; M. Harja Efendi; R. Didi Kuswara; Anis Syakiratur Rizki (Yayasan Tajuk Indonesia, 2024)
Ecoprint is a natural printing and coloring technique that is very easy to make and easy to obtain because this technique is environmentally friendly and does not harm the environment. This technique can use plants as basic materials in producing a variety of unique and interesting motifs. The purpose of this service activity is to provide artistic skills and skills in processing various types of plants in the Tolotongga environment into the main material for printing and coloring motifs on fabrics. The method used in this ecoprinting activity is to use training methods and direct practice on several communities in the Tolotongga Neighborhood, Bima City, West Nusa Tenggara. This activity starts from the stage of preparing tools and materials that will be used in ecoprinting then conducting training to the final result stage. The results of this training in the form of various motifs from the pounding technique applied to white t-shirts can be used.